The Gut Microbiome in Inflammatory Bowel Diseases: Diagnostic and Therapeutic Implications - Aden, Konrad (Visc Med, 2019)
The incidence of chronic inflammatory bowel diseases (IBD) is rising worldwide, and the interaction between the mucosal immune system and the intestinal microbiota is crucial for the understanding of these diseases. Due to new technologies, the data published on the intestinal microbiota has increased rapidly in the recent years. While many findings are descriptive, reporting associations between disease and microbial populations, recent advancement in technology made it possible to ask and answer more functional questions and to elucidate complex interactions between the intestinal microbiota and the mucosal immune system. In addition, first trials influenced the intestinal microbiota with the intention to treat IBD. This review summarizes aspects of the physiological function as well as the inflammation-induced changes of the gut microbiota and the association between the gut microbiota and pathogenesis in IBD. In addition, diagnostic and therapeutic options for treating IBD are reviewed.